NILAI BUDAYA INDIVIDUALISME DAN KOLEKTIVISME PADA KARAKTER DEKU DAN BAKUGO DALAM ANIME MY HERO ACADEMIA: DARI TANGGAPAN NETIZEN DI MEDIA SOSIAL - M. Dava Restu Ramandha; Desy Misnawati (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study looks at how the anime My Hero Academia shows individualistic and collectivistic values through the characters Deku and Bakugo, and how people online understand these values. The study uses existing research and a descriptive way of looking at things. The information used comes from scenes in the anime and comments from users on X and Quora. The study found that Deku shows collectivist values like caring for others and working together, while Bakugo shows individualism through being competitive and wanting to be in charge. People online have different reactions: some like Bakugo for being real, while others don't like that he is aggressive. Many people like Deku because he cares about others. In the end, the characters in the anime show cultural values that people understand in different ways based on their own experiences.